(untitled) (Research, Society and Development, 2021)
Adolescence is the main period in which individuals build their values, judgments and actions. The vulnerability inherent in the adolescence phase can be a risk for the use of psychoactive substances (SPA’s). The objective is to verify associations between socioeconomic factors and the moral development of adolescents and the predisposition to the use of psychoactive substances. One hundred adolescents, aged between 12 and 18 years, of both sexes and regularly enrolled in high school participated in the study. The socioeconomic questionnaire, CRAFFT/CESARE (acronym for Car; Relax; Alone; Forget; Family/Friends; Trouble) and the moral competence test were used. The collected data were analyzed using Pearson’s chi-square test (χ2) and the chosen significance level was 0.05. As for the results found, it was found that most of the sample is aged between 16-18 years, are female, have a paid job, practice physical activity and some religion. Regarding the preference of the stages of moral development, in the physician’s dilemma, there was a predominance of stages 1 and 2, in the judge, 5 and 6, and in the worker’s dilemma, stages 4 and 5. The highest level of morality supports the hypothesis that the paid function is protective against the use of SPA’s. Adolescents who practice a religion showed a higher level of moral competence compared to those who do not have a religion, in the worker’s dilemma, reaffirming the protective role of spirituality against the use of alcohol and other drugs.